Reviews - Lorraine Warren (Association for Learning Technology, 1994)
Europe in the Rotmdis a hypertextuall hypergraphical database of facts about Europe, biased towards education and training, but taking in its stride many peripheral areas relevant to anyone considering living and/or working in, or even visiting, a member state of the EU - population, economy, institutions, geography, climate and so forth - all making up thousands of interconnected screens. These screens contain maps with a selection of zooms and hotspots, all kinds of facts and figures about available educational and vocational courses (presented both textually and, where appropriate, as graphs, bar charts and such like), details of life in each EU member state, details of cities and what they have to offer, and a lot more. There are also extra facilities, such as being able to set currency exchange rates or to create customized notebooks.